Study on Some Physico-Chemical Characteristics of Ground Water of District Rampur - A Statistical Approach - Susheel Kumar Sindhu; Amit Sharma (E-Journal of Chemistry)
A systematic study has been carried out to explore the water quality index of ground water of various tehsils of Rampur district. Twenty five water samples from tube wells, open wells and hand pumps at various locations were collected and analyzed for pH, nitrate, turbidity, total dissolve solid, chlorides, total hardness, alkalinity and fluoride. In this study overall water quality of Rampur district is very poor and unsuitable for drinking purpose. Water quality of Bilaspur, Shahabad and Rampur city shows that water may not be used for drinking as well as domestic purpose. Present study recommends that the top priority should be given to water quality monitoring and indigenous technologies should be adopted to make water fit for drinking after treatment such as defluoridation, desalination.